2020
DOI: 10.21203/rs.3.rs-96935/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PDIA6 Contributes to Aerobic Glycolysis and Cancer Progression in Oral Squamous Cell Carcinoma

Abstract: Background/Objective: Accumulated evidence has demonstrated that aerobic glycolysis serves as a regulator of tumor cell growth, invasion and angiogenesis. Herein, we explored the role of protein disulfide isomerase family 6 (PDIA6) in the aerobic glycolysis and the progression of oral squamous cell carcinoma (OSCC). Methods: The expression pattern of PDIA6 in OSCC tissues was determined by qPCR and western blotting. Lentivirus and small interfering RNAs (siRNAs) were introduced into cells to upregulate and dow… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…PDIA6 belongs to the protein disulfide isomerase (PDI) family and is widely expressed in various types of human cancer, including breast cancer (32) and ovarian cancer (33). Increasing evidence suggests that PDIA6 is associated with the progression of various types of cancer (34)(35). For example, Kim et al (36) reported that inhibition of PDIA6 may transduce EGFR signaling by activating and inducing A disintegrin and metalloprotease 17 during the migration and invasion of U87MG glioblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…PDIA6 belongs to the protein disulfide isomerase (PDI) family and is widely expressed in various types of human cancer, including breast cancer (32) and ovarian cancer (33). Increasing evidence suggests that PDIA6 is associated with the progression of various types of cancer (34)(35). For example, Kim et al (36) reported that inhibition of PDIA6 may transduce EGFR signaling by activating and inducing A disintegrin and metalloprotease 17 during the migration and invasion of U87MG glioblastoma cells.…”
Section: Discussionmentioning
confidence: 99%